Optimising new mobility services - Dana Yanocha (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper presents a policy framework intended to maximize the benefits of dockless bike share through outcome-oriented system planning that includes monitoring and enforcement of regulations. Operational shortfalls of dockless bike share are categorised and several policy options for each category proposed. Finally, the paper identifies lessons and best practices from the rollout of dockless bike share systems around the world.
Keywords: 330; Verkehrspolitik; Radverkehr; Straßenverkehr; Share Economy; Welt